Authentic Leadership Questionnaire applied to Brazilian nurses: evidence of validity* - Maziero, Vanessa Gomes; Rocha, Fernanda Ludmilla Rossi; Campos, Juliana Alvares Duarte Bonini [UNESP]; Dias, Bruna Moreno; Balsanelli, Alexandre Pazetto; Gabriel, Carmen Silvia; Bernardes, Andrea (FapUNIFESP (SciELO), 2022)
Objective: to establish the psychometric properties of the Authentic Leadership Questionnaire (ALQ) applied to Brazilian nurses. Method: cross-sectional observational study with a non-probabilistic sample. The psychometric properties of the RATER and SELF versions of the ALQ were calculated using confirmatory factor analysis with the WLSMV robust estimation method. The following indices were used to assess the goodness-of-fit of the model: chi-square by degrees of freedom (χ2/df), Tucker-Lewis Index (TLI), Comparative Fit Index (CFI), Root Mean Square Error of Approximation (RMSEA) and Standardized Root Mean Squared Residual (SRMR). Data reliability was analyzed using the ordinal coefficient alpha and composite reliability. Results: 181 nurses participated of the study (female gender: 80.1%; mean age of 34.6 years; working time of less than five years: 76.3%). The complete ALQ RATER and ALQ SELF models did not present an adequate fit. Therefore, the refined models presented a better fit to the sample data (ALQ RATER: χ2/df=2.77; CFI=0.97; TLI=0.97; RMSEA=0.10; SRMR=0.05; ALQ SELF: χ2 / df=2.74; CFI=0.94; TLI=0.92; RMSEA=0.10; SRMR=0.08). In the ALQ RATER model, items 1, 7 and 13 were excluded. Due to the high correlation between the factors Relational Transparency and Moral Perspective, a three-factor model based on the combination of the factors mentioned above was proposed. In the ALQ SELF model, items 2, 5, 9 and 10 were excluded. Likewise, a three-factor model based on the combination of two factors, now called Self-Awareness Balance, was proposed. Conclusion: the data obtained with the Authentic Leadership Questionnaire with Brazilian nurses were valid and reliable.
Keywords: Health Services; Leadership; Nursing, Team; Organization and Administration; Psychometrics; Validation Study